The impact of Li2O concentration on mechanical and radiation attenuation properties of lithium zinc borotellurite glasses: an in silico study - Sahin, Meryem Cansu (Indian journal of physics, 2025)
This study aimed to investigate the gamma-ray protection factors and mechanical properties of five lithium zinc boro tellurite glasses with Li2O concentrations varying at 0, 5, 10, 15 and 20 mol% using GAMOS simulation and Phy-X/PSD software to provide theoretical insights. The mechanical moduli and radiation absorption properties, such as Young's modulus, bulk modulus, shear modulus, and longitudinal modulus, were examined using computational methods for five glass samples containing varying quantities of Li2O. Among all the glass samples, the sample containing 5 mol% Li2O has the largest linear and mass attenuation coefficient values. Moreover, the sample containing 5 mol% Li2O exhibits the most minimal half-value layer values in comparison to the other analyzed glasses. Samples containing 5% and 10 mol% Li2O reached comparable transmission factor values at 1, 3 and 5 cm thicknesses. Nevertheless, the sample containing 5 mol% Li2O exhibited exceptional radiation shielding characteristics.